Freeze-drying affects the starch digestibility of cooked potato tubers. (January 2018) - Larder, Christina E.; Abergel, Megan; Kubow, Stan; Donnelly, Danielle J.
Abstract: Freeze-drying (FD) has utility for phytonutrient screening but its reliability for starch measurements is unclear. The impact of FD was tested on total (TS), digestible (DS) and resistant starch (RS) for four potato varieties (PC Red, GG Red, GG Yellow, and Dolbec Yellow). The treatments included: (a) tubers boiled and then cooled for 1 h at room temperature (RT) (control; Treatment 1) and 24 h at 4 °C; (b) tubers boiled and then cooled for 1 h at RT with subsequent FD (Treatment 2); and (c) raw tubers that underwent FD, then were rehydrated, boiled, and cooled for 1 h at RT (Treatment 3). TS and DS content did not differ between the control samples cooled for 1 h or 24 h with Treatment 1 but RS content at 24 h was higher, which indicated starch retrogradation. Cultivar variations were observed in the percent increase in RS between 24 h vs. 1 h with the greatest increase in Dolbec Yellow (114.5 ± 7.6%). Relative to controls, FD treatments modified measured TS content in three of four varieties including overestimation by 94.2 ± 6.5% and 156.0 ± 5.2% for GG Yellow with Treatments 2 and 3, respectively. FD caused overestimation of DS and underestimation of RS in the same three varieties relative to controls including overestimation of DS in GG Yellow by 122.9 ± 4.7% (Treatment 2) and 205.7 ± 13.8% (Treatment 3). PC Red showed the greatest underestimation in RS content compared to controls of 42.5 ± 9.6% and 61.7 ± 5.4% in Treatment 2 and 3, respectively. Modifications to cooking and rehydration procedures following FD of raw tuber samples did not improve reliability of TS, DS, and RS measurements. Microscopy showed that cells remained intact following cooking whereas cell wall integrity was reduced when FD followed cooking and that cooking followed by FD led to destruction of cellular structure. We conclude that FD leads to unreliable starch measurements, which was supported by morphological microscopic evidence. For accuracy of starch profile measurements, the use of freshly cooked potato samples is essential. Graphical abstract: Highlights: Cooking followed by cooling increased resistant starch content at 24 h versus 1 h. Freeze-drying either after or prior to cooking led to unreliable starch results. Photomicroscopy showed that freeze-drying caused significant cellular damage.